Production of Sweet Corn (Zea mays saccharata Sturt) Bonanza Variety on Planting Distance Setting and The Use of NPK Fertilizer - Carolina Rosa Siallagan; Sutini Sutini; Didik Utomo Pribadi; Ramadhani Mahendra Kusuma (Future Science, 2021)
Sweet corn (Zea mays saccharata Sturt) cultivation can be done through variety selection technology use, fertilization, and the proper planting distance. One of the techniques used in sweet corn cultivation is planting distance and fertilization with NPK fertilizer. So, this study is critical in order to set the planting distance and NPK fertilizer dose to enhance sweet corn production. The goal of this study was to see how different planting distances and NPK fertilizer doses affected sweet corn production. The study was carried out in a rice field in Sambiroto Village, Padas District, at an elevation of ± 60 meters above sea level. It was conducted during January-May 2019. The method used was a factorial experiment with three replications based on a Randomized Block Design and two factors. The first factor is the planting distance, they are J1: 60 cm x 15 cm, J2: 60 cm x 20 cm, J3: 60 cm x 25 cm. The second factor is the NPK fertilizer dose, they are P0 = 0 kg / ha, P1 = 100 kg / ha, P2 = 200 kg / ha, P3 = 300 kg / ha. The results showed that (1) the J2 (60 x 20 cm) planting distance had the best effect on sweet corn cobs fresh weight per plant as well as per hectare without husks and sweet corn sugar content. (2) The NPK fertilizer dose of 300 kg/ha and planting distance of 60 x 20 cm resulted in optimal production on sugar content parameters. In conclusion, planting distance setting of 60 x 20 cm and NPK fertilizer dose of 300 kg / ha resulted in optimal production for sweet corn plant.